2016
DOI: 10.1080/14616734.2016.1170052
|View full text |Cite
|
Sign up to set email alerts
|

Rounding the bases with a secure base

Abstract: Parental availability and responsiveness were experimentally manipulated to determine the effects on children's athletic performance. Fifty children (3-12-year-olds) ran as fast as possible around a softball diamond twice: once while parents were available and responsive and once while parents were unavailable and unresponsive (engrossed in mobile phone; order randomized and counterbalanced). Children ran about three seconds faster and were 17% less likely to trip, fall, or false start in the parental availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
11
0
3
Order By: Relevance
“…In turn, distracted parents may have children that form a more insecure attachment with the parent. These concerns have been raised by a number of researchers (e.g., McDaniel & Coyne, ; Radesky & Christakis, ; Stupica, ), although no research has directly linked parent phone distraction with child attachment security as of yet.…”
Section: How Does Parent Phone Use Impact Children?mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, distracted parents may have children that form a more insecure attachment with the parent. These concerns have been raised by a number of researchers (e.g., McDaniel & Coyne, ; Radesky & Christakis, ; Stupica, ), although no research has directly linked parent phone distraction with child attachment security as of yet.…”
Section: How Does Parent Phone Use Impact Children?mentioning
confidence: 99%
“…Another interesting piece of evidence deals with sports performance. In observational data, it was found that children perform better at sports when their parents paid attention to them and worse when their parents used their phone (Stupica, ).…”
Section: How Does Parent Phone Use Impact Children?mentioning
confidence: 99%
“…While there is a growing interest in the effects of technology on parent-child interactions, research has primarily focused on the consequences of parents' digital distraction for children's developmental processes (e.g., Radesky et al, 2014;Stupica, 2016). Research on the effects of digital distraction on parents' own experience with their children is much scarcer, with only a few qualitative and ethnographic studies shedding some light on this topic (e.g., Blackwell, Gardiner, & Schoenebeck, 2016;Mazmanian & Lanette, 2017).…”
Section: Phone Use and Parentingmentioning
confidence: 99%
“…A new line of research investigates the link between media use of parents and behavioral difficulties of children. In cross-sectional studies, parent mobile technology use in the presence of the child has been shown to be associated with lower parental responsiveness, sensitivity, and attention [13,14], with more hostility [15], and, possibly as a consequence, with more risky and less attentive behavior in children [16,17]. Media use of mothers could also be linked to media use of children [18,19].…”
Section: Introductionmentioning
confidence: 99%